Beacon-based meeting attendance using mobile application / Mohammad Nazirul Zainal - Zainal, Mohammad Nazirul (2019)
Nowadays, an organization will make a meeting once a week to share the report to the top management. So, the attendance towards the employee to attend the meeting are crucial. The recent attendance meeting system is not so efficient to be used on this era because it need to key in the data manually. Next, the problem that occur towards the system is that the participants need to wait for a long time just to take the attendance because of long queue. Subsequently, the system cannot monitor the lecturer from in and out the meeting place or snaking from the meeting after the attendance had been taken. Therefore, beacon-based mobile application meeting attendance was developed to assist or ease the work on to take the attendance more efficiently compare to recent system. On this project it will used method using beacon-based that interact with the user mobile smartphone that have been installed. The sensor will scan the IMEI number for the phone and will key in directly inside the database of meeting. The result of the project is that it can make the participant’s attendance been taken will be more easily and fast. This project should at least help the process of taking the attendance more efficient.